2019
DOI: 10.1039/c8ta10513h
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-ion batteries: outlook on present, future, and hybridized technologies

Abstract: Key insights into the evolution of lithium-ion batteries: present, future, and hybridized technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
896
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,652 publications
(907 citation statements)
references
References 211 publications
4
896
0
7
Order By: Relevance
“…Oxide based‐cathode materials were proven to be efficient for Li‐ion battery . Naturally, some of these oxides has been investigated for Mg‐ion battery.…”
Section: Figurementioning
confidence: 99%
“…Oxide based‐cathode materials were proven to be efficient for Li‐ion battery . Naturally, some of these oxides has been investigated for Mg‐ion battery.…”
Section: Figurementioning
confidence: 99%
“…Rechargeable lithium‐ion batteries (LIBs) are the most widely used electrochemical energy storage devices. They combine stable capacity retention with good energy density and efficiency, making them first choice for a variety of applications, such as in electric vehicles . Nevertheless, especially energy‐demanding applications necessitate the development of new low‐voltage anode and high‐voltage cathode materials with improved specific capacities (where energy storage is based on some form of battery storage, such as insertion, conversion or alloying reactions) .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Ni 2 P is an attractive anode material because of its low potential versus Li/Li + and high theoretic capacity of 542 mAh g −1 compared with graphite . However, during the ion insertion/extraction processes, these anode materials often suffer from large volume variation and low electronic/ionic conductivity . Therefore, designing stable electrode materials with high conductivity is of great significance for the development of high‐performance LIBs.…”
Section: Introductionmentioning
confidence: 99%